Technical and economic evaluation of photovoltaic system connected to the network, for broiler poultry houses - Justina, Natã Della; Siqueira, Jair Antonio Cruz; Tokura, Luciene Kazue; Villa, Bruna de; Tokura, Willian Isao; Silveira, Vander Fabio; Rodrigues, Hamom Ventura (Latin American Journal of Energy Research, 2022)
With the poultry market expanding, companies started to worry about increasing the efficiency of the production process, giving space to the automation of poultry houses, to meet the market demand. On the other hand, the automated comfort systems used in poultry houses have great demand for electricity, generating one of the highest costs of Brazilian poultry production. Given the above, the use of renewable energy systems can be of great importance for the poultry sector. Thus, the objective of the work was to dimension and economically evaluate a photovoltaic system connected to the network to meet the demand demanded by broiler poultry houses, in the city of Santa Izabel do Oeste, state of Paraná. Subsequent to the dimensioning of the system, the study of its economic viability was carried out, using the values ​​made available by companies in the industry, using the Payback technique for the study and evaluation of the economic viability of the system. The dimensioning of the methodology employed resulted in a system composed of 342 modules of 270 Wp, polycrystalline, with 3 inverters of 30 kWp. Economic viability showed a Payback time of 4 years, with an IRR of 30.02%. The results allowed us to conclude that there is a good technical and economic feasibility for installing the system.
Keywords: rural energization; photovoltaics; sustainability; broiler poultry houses; payback